Impact of industrial activities on heavy metal loading and their physico-chemical effects on wetlands of lake Victoria basin (Uganda) - Muwanga, A.; Barifaijo, E. (My University, 2006)
The diverse functions of wetlands are being adversely affected by human activities. This paper discusses the impact of these activities on heavy metal loading in different media within the wetlands. Water and sediment/soil samples were taken from areas with active industrial activities and from an area where there is no industrial activity. Sources of water pollution include effluents from a brewery (high pH) and areas associated with tanning activities, sewage treatment plant and former copper smelter (high electric conductivity values). Effluents from a battery assembly plant, water treatment plant, pharmaceutical industry and former copper smelter have relatively high Pb values (up to 1.4 ppm) otherwise most heavy metal concentrations are below maximum acceptable limits for water. This calls for mitigation measures. In sediments, high heavy metal values were associated with battery and metal fabricating industry (Pb), operations involving Zn scrap (Cd), former Cu smelter (Cu, Pb, Ni and Co), tannery and pharmaceutical industry (Cr), and soap and cosmetics industry (Hg). Fish have low levels of Hg. However, fish is known to bioaccumulate Hg through methylation, may cause increase in the Hg in the food chain. Industries which release effluents with high heavy metal contents should treat them before discharge.
Keywords: Wetlands, Lake Victoria basin, heavy metals, physico-chemical parameters, toxicity, bioaccumulation.